PTU-178 Pitfalls of Faecal Elastase Estimation. (4th June 2013) - Shah, R; Varma, A; Thomson, S; Direkze, N
Abstract : Introduction: The faecal elastase test measures the concentration of the elastase-3B enzyme found in faecal matter with an enzyme-linked immunosorbent assay (ELISA). It is a good indicator of exocrine pancreatic status, and is less invasive and expensive than the secretin-cholecystokinin test, the current gold standard. Levels of faecal elastase lower than 200 μg/g of stool indicate an exocrine pancreatic insufficiency (EPI). Methods: Aim: Faecal elastase is a marker for EPI particularly in chronic pancreatitis and pancreatic malignancy. Our aim was to outline the value of faecal elastase in patients with obscure diarrhoea. Methods: We retrospectively collected data of patients who had a faecal elastase test from June 2010 to 2012. We correlated the abnormal results with symptoms, findings on imaging and response to treatment. We also stratified these findings in patients with ultra low faecal elastase to assess whether the diagnostic yield was different. Paediatric patients were excluded from the study. Results: There were a total of 72 abnormal results out of 523 in this 2 year study of which 33 (45%) patients had large volume diarrhoea. Of these, 26 (78%) patients had no therapeutic response to pancreatic enzyme supplements (PES) and had normal imaging, 4 had a response and in 3 we could not establish whether PES was trialled. Of the patients who responded to treatment, 2 had imaging suggestive of chronic pancreatitis. 9 of the patients who were investigated for steatorrhoea were on statins but had normal faecal elastase, normal cross sectional imaging and good response to treatment with PES 41 patients had ultra low faecal elastase levels ( < 50µg/g), of these 32(78%) patients had significant pancreatic pathology whilst only 9(22%) had watery diarrhoea. Conclusion: 1- A normal faecal elastase does not exclude EPI – as the 9 patients who were on statins had normal faecal elastase and pancreatic imaging and a dramatic response to PES. Other drugs like azathioprine, steroids causing EPI needs further investigation. 2- An ultra-low faecal elastase level (<50 µg/g), is more likely to be related to significant pancreatic pathology with a response to treatment. Patients with watery diarrhoea are less likely to have a level this low. In these patients stool lyophilising or concentration should be performed before faecal elastase estimation. 3- In our patient group conditions like diabetes, coeliac disease, Addisons disease, gastrointestinal fistulas, short bowel syndrome, microscopic colitis, bile salt malabsorption and previous radiation all lead to falsely low levels without clinical correlation or response to treatment. Faecal elastase in this sub group should be interpreted with caution. Disclosure of Interest: None Declared. Reference: The role of faecal elastase-1 in detecting exocrine pancreatic diseaseJohn S. Leeds, Kofi Oppong & David S. Sanders